TATA CARA PENULISAN NASKAH ILMIAH - B. P. Sitepu (Jurnal Ilmiah Visi, 2009)
The experience in managing articles to be published in some journals indicates, many writers do not meet the requirements for scientific or academic writings. Some of the articles must be returned to the writers to be reorganized and rewritten based on the house style of the journal. This surely takes time and delays the publishing process.This article therefore discusses the requirements for an article to be published in a journal, including the techniques how to write the title, abstract and structure of the article in general. For the house style of each journal, the writer is suggested to follow the writing guides issued by the journal which is intended to publish the article.